Religiosity and personal well-being: People can be happy with or without religion - Matthias Opfinger (Kiel Institute for the World Economy (IfW), 2010)
Despite all economic and social transitions that have occurred in the last centuries we still find that people go to church. Somehow religious beliefs have not vanished over time. Since there is no material reward for going to church or praying religiosity has to create utility through other means. It could raise peoples' personal well-being. In this paper we use information from the World Values Survey about subjective happiness and life satisfaction. We relate this information to revealed religiosity and measure if religiosity makes people happier. We use different methods and also control for economic factors, family matters, health, and democracy. The key finding is that there seems to be a U-shaped relationship between personal well-being and religiosity, especially so for happiness. This result is consistent throughout all our estimations. Our analysis also gives hints that higher income might lead to higher subjective well-being.
Keywords: 330; Personal well-being; happiness; life satisfaction; religiosity; U-shaped relationship; Religion; Lebenszufriedenheit; Lebensstandard; Schätzung; Welt